Instructional development needs for web-based education in higher education - Thienhuong Hoang (Penerbit Universiti Kebangsaan Malaysia, 2010)
Over the past decade, web-based education programs have developed at an extraordinary rate. Web-based education has emerged in higher education as a means for providing a variety of educational opportunities to a diverse community of individuals. As the number of participants continues to increase, so too does the importance of providing effective instruction that focuses on the needs of learners. The purpose of this study was to identify directions for addressing the instructional development needs that instructor-practitioners teach when using web-based communication tools in higher education. This single case study aimed to examine the factor structure of a 16-item survey. The data in the areas of instructional development and net-based learning. The findings indicated a four-factor model for instructional development concerned with web-based courses: (1) technical (internet/Web resources); (2) social (interpersonal); (3) moderating (cognitive/pedagogical); and (4) management (teaching). The identified constructs were associated with the unique characteristics of teaching courses using web-based communication tools. Support for instructors should be offered in the areas of basic and essential skill development (e.g., technical matters related to web-based communication tools) and delivered in ways that are embedded in effective pedagogical practices